1998
DOI: 10.1128/aac.42.4.895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacterial Biofilm Formation on In Vitro and In Vivo Activities of Antibiotics

Abstract: The impact of bacterial adherence on antibiotic activity was analyzed with two isogenic strains of Staphylococcus epidermidis that differ in the features of their in vitro biofilm formation. The eradication of bacteria adhering to glass beads by amikacin, levofloxacin, rifampin, or teicoplanin was studied in an animal model and in a pharmacokinetically matched in vitro model. The features of S. epidermidis RP62A that allowed it to grow on surfaces in multiple layers promoted phenotypic resistance to antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 28 publications
2
72
0
8
Order By: Relevance
“…It is therefore highly desirable to establish assay systems which predict the clinical outcome from susceptibility tests with better correlation than standard susceptibility assays for MIC and MBC determination using planctonic cells or cells growing under optimized conditions on solid media [6,13,16,24,39,40]. Therefore new techniques have been developed to study susceptibility of biofilm populations [1,2,5,7,8,12,17,22,42,48,49] with differences and difficulties in respect of handling and comparability. In this study we developed a versatile method for rapid antibiotic susceptibility screening for both attached S. epidermidis cells and cells integrated in a biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore highly desirable to establish assay systems which predict the clinical outcome from susceptibility tests with better correlation than standard susceptibility assays for MIC and MBC determination using planctonic cells or cells growing under optimized conditions on solid media [6,13,16,24,39,40]. Therefore new techniques have been developed to study susceptibility of biofilm populations [1,2,5,7,8,12,17,22,42,48,49] with differences and difficulties in respect of handling and comparability. In this study we developed a versatile method for rapid antibiotic susceptibility screening for both attached S. epidermidis cells and cells integrated in a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MIC and MBC values of staphylococci often do not correlate with the clinical outcome of antibiotic treatment of medical deviceassociated infections in clinical practice, as is also demonstrated in different animal models [6,13,16,24,39,40]. Several techniques with differences and difficulties in respect to handling and standardization of in vivo grown biofilms have been used to study antibiotic susceptibility of biofilm populations [1,2,5,12,17,22,42,48,49]. Many systems used are effective models of biofilm formation but they are not suitable for rapid susceptibility testing in a clinical laboratory setting.…”
mentioning
confidence: 91%
“…Although many in vivo models for biofilm infections have been described in the literature, a vascular graft infection model with Staphylococcus epidermidis was chosen for the study since vascular grafts are very prone to biofilm formation (24)(25)(26). Vascular grafts are usually made of PTFE, one of the most commonly used biomaterials and are known to be affected by biofilm causing bacteria (24,27) and any morphologic changes on the prosthetic device are detectable Control (n ‫ס‬ 6) 6/6 6/6 IM (n ‫ס‬ 6) 4/6 a 4/6 a Implant (n ‫ס‬ 6) 0/6 b 1/6 b a 2 analysis showed that the number of rats with purulent discharge and discolored prosthetic device was not significantly different between the control group and IM group.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of pathogens to adhere to the implant surface depends for instance on the type and structure of bacteria, their ability to secrete mucin and the physical and chemical characteristics of the graft. Biofilm formation plays a crucial role in establishing a biomaterial-associated infection [11].…”
Section: Discussionmentioning
confidence: 99%